PVAT and Its Relation to Brown, Beige, and White Adipose Tissue in Development and Function - Hildebrand, Staffan; Stümer, Jasmin; Pfeifer, Alexander (Frontiers in Physiology, 2018)
Adipose tissue is commonly categorized into three types with distinct functions, phenotypes, and anatomical localizations. White adipose tissue (WAT) is the major energy store; the largest depots of WAT are found in subcutaneous or intravisceral sites. Brown adipose tissue (BAT) is responsible for energy dissipation during cold-exposure (i.e., non-shivering thermogenesis) and is primarily located in the interscapular region. Beige or brite (brown-in-white) adipose tissue can be found interspersed in WAT and can attain a brown-like phenotype. These three types of tissues also have endocrine functions and play major roles in whole body metabolism especially in obesity and its co-morbidities, such as cardiovascular disease. Over the last years, perivascular adipose tissue (PVAT) has emerged as an adipose organ with endocrine and paracrine functions. Pro and anti-inflammatory agents released by PVAT affect vascular health, and are implicated in the inflammatory aspects of atherosclerosis. PVAT shares several of the defining characteristics of brown adipose tissue, including its cellular morphology and expression of thermogenic genes characteristic for brown adipocytes. However, PVATs from different vessels are phenotypically different, and significant developmental differences exist between PVAT and other adipose tissues. Whether PVAT represents classical BAT, beige adipose tissue, or WAT with changing characteristics, is unclear. In this review, we summarize the current knowledge on how PVAT relates to other types of adipose tissue, both in terms of functionality, developmental origins, and its role in obesity-related cardiovascular disease and inflammation.